Unveiling the Veil of Black Money Understanding Its Impact on Economic Stability and Policy Formulation in India - Gourav Kumar Sharma (Recent Trends in Social Studies, 2025)
The issue of black money has emerged as a critical concern for India, undermining economic stability and challenging the effectiveness of policy formulation. Black money, generated through unaccounted income and tax evasion, exerts a detrimental influence on multiple facets of the economy, including resource allocation, income distribution, and public trust in governance. This study examines the multifaceted impact of black money on India’s economic framework, highlighting its role in distorting markets, fostering inequality, and impeding sustainable growth. By exploring the sources and channels of black money circulation, the research delves into its pervasive effects on inflation, investment, and employment. It critically evaluates the effectiveness of measures implemented by the Indian government, such as demonetization, the Goods and Services Tax (GST), and anti-money laundering frameworks, in curbing the menace of black money. Additionally, the study emphasizes the importance of leveraging technological advancements, such as blockchain and artificial intelligence, to enhance transparency and detection mechanisms. Through a comparative analysis of global practices and lessons for India, the research provides actionable recommendations for policy reform. This comprehensive analysis seeks to offer insights into addressing the challenges posed by black money while fostering economic stability, equitable development, and robust governance in India.
Keywords: Black money; Economic stability; GST; blockchain; demonetization; financial transparency; policy formulation; tax evasion